A Proxy Communication Method in Machine‐to‐Machine System to Enable the Device Connection to Different Multiple Services and Its Implementation. Issue 12 (December 2013) - Kitagami, Shinji; Kaneko, Yosuke; Yasuda, Akihisa; Minemura, Harumi; Koizumi, Hisao
SUMMARY The use of machine‐to‐machine (M2M) systems has spread among people seeking to connect devices with remote systems via the Internet to provide services such as remote maintenance and remote energy management without human intervention. For the access network for M2M systems, not only security and immediacy, but also multiservice connectivity is required, which makes it possible to connect devices with multiple services. In this paper, an M2M proxy communication method is proposed as a communication method that achieves multiservice connectivity and security and immediacy at the same time. In the proposed method, a proxy server located between devices and application servers relays communications among them. In the relay processing, multiservice connectivity of the access network is achieved by performing access or exclusive control to devices. By adopting the M2M proxy communication method, the access network simultaneously provides multiservice connectivity, security, and immediacy at low cost without introducing any special scheme into devices. © 2013 Wiley Periodicals, Inc. Electron Comm Jpn, 96(12): 74–84, 2013; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/ecj.11474